Distribution, Characteristics, and Use of Earth Dens and Related Excavations by Polar Bears on the Western Hudson Bay Lowlands - Clark, D.A.; Stirling, Ian; Calvert, Wendy (ARCTIC, 1997)
Polar bears fasting on land along the western coast of Hudson Bay during the open water period, from late July through early November, excavate three different types of structures, which we termed pits, deep dens, and shallow dens. Pits were shallow excavations found on the tops of banks or beach ridges, whereas both deep and shallow dens were dug into frozen peat banks. Pits were used as temporary resting places. The function of shallow dens is less clear, although some bears have been observed resting in them. Deep dens, which have an entrance tunnel and an enlarged inner chamber, are similar in size and structure to maternity dens dug in snow by female poplar bears elsewhere in their range. Deep and shallow dens are primarily occupied by lone females, most of which are pregnant, while pits are generally occupied by adult males and are used more during summer than in autumn. Pregnant polar bears in western Hudson Bay give birth between mid-November and mid-December, by which time snowdrifts suitable for the construction of maternity dens have not yet formed in most years. Thus, because earth dens represent the only consistently suitable environment available at the time of parturition, we suggest most cubs in western Hudson Bay are born in them. Consequently, the availability of suitable habitat for the construction and use of earth dens is probably critical to the survival of the polar bear population in Western Hudson Bay. Secondary benefits of earth dens to pregnant females, and to other bears during the warm weather in late summer, are that they help the bears to conserve energy by remaining cool and to avoid insect harassment. Les ours polaires qui jeûnent sur la terre ferme le long de la côte occidentale de la baie d'Hudson durant la période d'eau libre (fin juillet à début novembre), creusent trois types de structures différentes que nous appelons fosses, tanières profondes et tanières peu profondes. Les fosses sont des creux peu profonds que l'on a trouvé en haut des talus ou des crêtes de plage, ...